(untitled) (Advances in Civil and Architectural Engineering, 2025)
This study evaluates the impact of geotextile installation on the stability of a sand embankment under the influence of water seepage. For the embankment, uniform river sand was used from the lower course of the Drava River, while a non-woven geotextile, commonly used in hydraulic engineering works was selected. Five physical models at a reduced scale were built in the HM 169 apparatus, where the geotextile was installed in different configurations. The aim of the study was to determine the effect of different geotextile configurations on the stability of embankment slopes. The models exhibited different behaviours under seepage influence, ranging from very rapid failure in the case where no geotextile was present in the embankment, gradual failure with the application of geotextile without wrapping, to stability without change when geotextile was wrapped. The behaviour observed in the physical models was then simulated with numerical models using GeoStudio software. The goal of the numerical analyses was to determine an appropriate method to define slip surfaces and identify a suitable method to account for the influence of geotextile. The positive influence of the geotextile on stability was considered using various methods implemented in GeoStudio software: 1. as a standard reinforcement element, 2. by simulating a positive contribution of the geotextile with external forces (continuous load). The standard reinforcement element did not yield satisfactory results due to the position of the geotextile relative to the predefined critical slip surface. As the geotextile wrapped around the downstream slope, continuous load proved to be a better option for simulating its effect.